Analisis Peran Etnosentrisme Dan Lingkungan Sosial Budaya Pada Pemasaran Internasional - Siti Mamlu’atur Rohmah; Sribawon Nur Fadillah; Vicka Nindyasari; Yulia Tri Nurhasanah; Zakiyyah Sekarsari Darajad (Journal Of Business, Finance, and Economics (JBFE), 2023)
This study aims to determine the impact of ethnocentrism and the socio-cultural environment on international marketing strategies. This research uses a library research method, where information comes from several journals and books. Furthermore, the data that has been collected will be processed and analyzed with various other research results to produce a new idea. Ethnocentrism is the attitude and mindset of a group that considers its group the best compared to other groups. The purpose of socio-culture is to maintain national identity, diversity, improve intercultural relations, improve education and knowledge and for socio-economic development. International marketing is a marketing activity that seeks to enter borders between countries. The results of this study found that when doing international marketing must be able to adjust the challenges, namely socio-culture and ethnocentrism and the development of relevant communication. If you are able to analyze the cultural characteristics of the destination country, it will open up opportunities for acceptance of products originating from outside the country.